Consumer acceptability of stabilized peanut butter - Rodrigueza, Maria Rona Chavez; Galvez, Flor Crisanta F. (1999.)
The consistency and spreadability of 18 formulated and three commercially available peanut butters were evaluated using consumer acceptance tests. The effect of roasting time, level of stabilizer, and conditioning on the acceptability of consistency and spreadability of the formulated peanut butters were studied. Statistical analysis of the data, at 5% level of significance, showed that stabilized commercially produced peanut butter and peanut butter with 1% level of stabilizer were more accepted that unstabilized peanut butter and those having 0.5% level of stabilizer. The results obtained indicated that stabilized peanut butter have more acceptable consistency and spreadability compared to unstabilized peanut butter product. Different roasting time and conditioning did not appear to significantly affect the consistency of peanut butter. Spreadability of peanut butter, however was shown to have been affected by the roasting time and conditioning and level of stabilizer.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Peanut butter